2017
DOI: 10.1155/2017/3120854
|View full text |Cite
|
Sign up to set email alerts
|

Ending Preventable Child Deaths from Pneumonia and Diarrhoea in Afghanistan: An Analysis of Intervention Coverage Scenarios Using the Lives Saved Tool

Abstract: Background. Despite improvements in child health, Afghanistan still has a heavy burden of deaths due to preventable causes: 17% of under-5 deaths are due to pneumonia and 12% are due to diarrhoea. Objective. This article describes the situation of childhood pneumonia and diarrhoea in Afghanistan, including efforts to prevent, protect, and treat the two diseases. It estimates lives saved by scaling up interventions. Methods. A secondary analysis of data was conducted and future scenarios were modelled to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Afghanistan is one of the worlds affected regions in the world, both in terms of health standards of living. It is a country having the highest IMR poverty rates and other socio-demographic indicators [54,55]. Diarrheal disease still claims the lives of 26 children each day across the country, accounting nearly 12% of deaths in Afghanistan [56].…”
Section: Discussionmentioning
confidence: 99%
“…Afghanistan is one of the worlds affected regions in the world, both in terms of health standards of living. It is a country having the highest IMR poverty rates and other socio-demographic indicators [54,55]. Diarrheal disease still claims the lives of 26 children each day across the country, accounting nearly 12% of deaths in Afghanistan [56].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies explicitly targeted children under 5 or 2 years of age and studies of household interventions specifically targeted women and young children. Interventions ranged from nutrition awareness and health promotion activities [62,63,75,79], micronutrient deficiency treatment or prevention [50,[65][66][67]80], malnutrition treatment or prevention [68, 70-72, 77, 78], and delivery or modelling of a package of community and facility-based interventions, including multisectoral approaches [64,69,74,76,81].…”
Section: Nutrition Programme Responses and Multisectoral Approachesmentioning
confidence: 99%
“…Two studies used the Lives Saved Tool to model the impact of a combination of IYCF interventions, community-based health and nutrition interventions, and WASH on improving child health and nutrition outcomes. Akseer et al (78) and Higgins-Steele et al ( [76]) found significant regional variations in coverage and inequalities and that better modelling tools are needed to adequately capture the spectrum of nutrition-sensitive and nutrition-specific interventions and their impacts on child mortality.…”
Section: Delivery or Modelling Of A Package Of Community And Facilitymentioning
confidence: 99%
“…Child and maternal mortality remain critical public health issues, with higher rates in rural settings compared to urban 3 . Though some newborn and child health statistics have improved, immunization and nutrition indicators lag behind other countries regionally and vary markedly [3][4][5] between provinces and urban and rural settings. Total fertility rate (TFR) among Afghan women, which contributes to maternal mortality, is also high at 5.3 children per woman, and age at first birth is low (median 20.1 years) with 12% of girls ages 15-19 years initiating childbearing 3 .…”
Section: Introductionmentioning
confidence: 99%